Financial distress and customer-supplier relationships - Lian, Yili (Journal of Corporate Finance, 2017)
Using a customer-supplier matched sample from 1980 to 2014, I study the role of customer-supplier relationships on suppliers' financial distress. If a significant amount of a supplier's sales is tied to a major customer, the supplier's financial health is influenced by the major customer's financial conditions. I find that a supplier's probability of financial distress is positively related to its major customer's financial distress status. This relation persists up to two years after a major customer is in financial distress. Further, I show that the relationship is more pronounced when customer-supplier relationships are stronger, when a major customer is more likely to fail in the future, and when the supplier makes unique products. The results highlight the importance of understanding customer-supplier relationships when analyzing a firm's probability of financial distress.